Work-related psychological health and psychological type: A study among primary school teachers in Wales. Issue 4 (4th July 2019) - Francis, Leslie J.; Lankshear, David W.
Abstract: This study examines the connection between the balanced-affect model of work-related psychological health and psychological type among a sample of 260 primary school teachers in Wales. This sample of teachers comprised more extraverts (59%) than introverts (41%), more sensing types (77%) than intuitive types (23%), more feeling types (60%) than thinking types (40%) and more judging types (90%) than perceiving types (10%). The data demonstrated that introverts experienced higher levels of emotional exhaustion than extraverts (negative affect) and that intuitive types and feeling types experienced higher levels of satisfaction in teaching than sensing types and thinking types (positive affect). The implications of these findings are discussed for promoting good work-related psychological health among primary school teachers.